Determinación anatomopatológica de posibles causas de muerte entre noviembre del 2016 a enero del 2018 en anfibios del Centro de Conservación Balsa de los Sapos - Galante Mulki, María Cristina (2018)
The loss of biodiversity due to anthropic influence is a growing problem that has diminished the populations of Ecuadorian amphibians. It is for this reason that this study aimed to determine, identify and classify the macro and microscopic lesions present in deceased adult toads that died from 29/11/2016 to 01/31/2018 in the institution “Balsa de Sapos” to establish the possible causes of death and their frequency. For this purpose, recently deceased animals were collected, fixed in 10 percent formalin and examined by necropsy and histopathology. The histopathological plates were stained with Hematoxylin-Eosin and examined by optical microscopy. The observed alterations were compared with bibliography and analyzed by descriptive statistics. The main observed lesions were congestion (16/20 equal 80 percent); active melanomacrophages (14/20 equal 70 percent); valvular endocarditis (10/20 equal 50 percent), hydropericardium, end-stage kidney, hepatic lipidosis, hepatitis, hemorrhage, subcutaneous mycosis (2/20 equal 10 percent); interstitial myocarditis, chronic bronchiolitis (11/20 equal 55 percent); constrictive pericarditis, valvular hemorrhage, renal carcinoma, tubulorhexis, preneoplastic cholangitis, peri-portal interface, liver cirrhosis, rhabdomyolysis, hepatic hydropic degeneration, stress myopathy, cutaneous spongiosis, Munro’s microabscesses, chronic pressure ulcer carcinoma, serous atrophy of the fat, enteritis (1/20 equal 5 percent); eccentric cardiac hypertrophy, proteinuria, exudative pneumonia, micro and macrovesicular hepatic change (8/20 equal 40 percent); valvular fibrosis, membranoproliferative glomerulonephritis, gallstones, mono and polyphasic degenerative myopathy (5/20 equal 25 percent); lambertosis, tubulointerstitial nephritis, neutrophilic cholangitis, gastritis (6/20 equal 30 percent); proliferative pneumonia (13/20 equal 65 percent); proliferative glomerulonephritis (12/20 equal 60 percent); glomerulosclerosis, gallbladder hydrops, osteodystrophies, gastric erosion (4/20 equal 20 percent); edema (17/20 equal 85 percent); chronic dermatosis (9/20 equal 45 percent) and inflammatory dermatosis (3/20 equal 15 percent). These findings indicated that the anurans died due to potential infectious diseases (10/20 equal 50 percent), infectious (4/20 equal 20 percent) and non-infectious causes (6/20 equal 30 percent). In conclusion, most of the lesions are chronic and associated with infectious diseases or cardiovascular alterations due to stress or environmental hypoxia.